The Role of Islamic Boarding Schools In Developing Attitude and Morals of Cimahi City Students Of STAI Al-Musdaryah - Laela Nasrani, Silvia; Irwansyah, Shindu (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to establish the role of Islamic boarding schools in developing the attitudes and morals of students at STAI Al-Musdariyah Cimahi City. The research uses qualitative analysis methods. Where the data is obtained and analyzed using qualitative methods to gain a comprehensive understanding of the research subject. Several descriptions are used to discover principles and explanations that lead to conclusions. Then data is collected using accurate observations, including descriptions in detailed context accompanied by detailed interview notes. The data used is secondary data obtained from the results of a questionnaire published by the author to students of STAI Al-Musdariyah Cimahi City. This subject concerns the decline in attitudes and morals of the younger generation which is currently caused by an unconducive environment and a lack of order in the social environment in controlling existing social changes, and in the end, it can hurt them. All problems experienced by the younger generation r